2016
DOI: 10.1007/s11095-016-1962-9
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Hypoxia-Inducible Heme Oxygenase-1 Gene for Site-Specific Gene Therapy in the Ischemic Stroke Animal Model

Abstract: pEpo-SV-HO-1 induced HO-1 gene expression and therapeutic effect in the ischemic brain. Therefore, pEpo-SV-HO-1 may be useful for site-specific gene therapy of ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In a rat MCAO model using stereotaxic instrumentation, treatment with an adenoviral vector overexpressing HO-1 resulted in decreased infarct volume and attenuation of neurologic deficits [27]. Because of the deleterious side effects of viral vectors, such as immunogenicity and oncogenicity [28], non-viral gene carriers have been investigated and were shown to induce site-specific HO-1 gene expression and therapeutic effect when applied as stereotaxic injection into the rat ischemic brain [29]. HO-1 gene transfer into injured carotid arteries of ApoE-null mice led to earlier thrombolysis with decreased plasminogen activator-1 expression [30].…”
Section: The Ho-1 Pathway and Ischemic Stroke: Preclinical Resultsmentioning
confidence: 99%
“…In a rat MCAO model using stereotaxic instrumentation, treatment with an adenoviral vector overexpressing HO-1 resulted in decreased infarct volume and attenuation of neurologic deficits [27]. Because of the deleterious side effects of viral vectors, such as immunogenicity and oncogenicity [28], non-viral gene carriers have been investigated and were shown to induce site-specific HO-1 gene expression and therapeutic effect when applied as stereotaxic injection into the rat ischemic brain [29]. HO-1 gene transfer into injured carotid arteries of ApoE-null mice led to earlier thrombolysis with decreased plasminogen activator-1 expression [30].…”
Section: The Ho-1 Pathway and Ischemic Stroke: Preclinical Resultsmentioning
confidence: 99%
“… 8 Experimental models simulating brain ischemia demonstrated that augmenting HO‐1 expression through gene therapy led to reduced infarct volume and alleviation of neurological impairments. 16 , 34 Additionally, HO‐1's downstream metabolites may also exert a protective effect in ischemic stroke. CO exerts a potent anti‐inflammatory effect in diverse diseases, and biliverdin is subsequently transformed into bilirubin, 35 which can function as an antioxidant.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature suggests that HO‐1 may protect ischemic stroke through its anti‐inflammatory, antioxidant, antiapoptotic, and vasorelaxant effects by degrading the oxidant heme 8 . Experimental models simulating brain ischemia demonstrated that augmenting HO‐1 expression through gene therapy led to reduced infarct volume and alleviation of neurological impairments 16,34 . Additionally, HO‐1's downstream metabolites may also exert a protective effect in ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Various treatments are being tried to improve outcomes in ischemic stroke, but most of these treatments are based on drugs such as tPA. Recently, attempts have been made to treat ischemic brains by using gene therapies to regulate HO‐1 gene expression (Choi et al, 2016), inhibit the NLRP3 inflammasome (Zhu et al, 2021), deliver OPA1‐ΔS1 to affected tissues (Lai et al, 2020), or utilize glial cell line‐derived neurotrophic factor (GDNF) and hepatocyte growth factor (HGF) to reduce tissue damage (Shang et al, 2010; Yamashita & Abe, 2016; Yamashita et al, 2009). However, no previous studies have targeted early ischemic damage in glia using a therapeutic nanoparticle approach.…”
Section: Discussionmentioning
confidence: 99%